El territorio y las reformas constitucionales de Rafael Reyes - Londoño Vélez, Omaira (2023)
A country‘s land organization should respond to the relationship between the state‘s population and territory, as well as to a project built collabo ratively by the diverse groups that make up society. Land organization in Colombia has not met these expectations; on the contrary, it has swayed according to the conflicts staged by the parties in power. This paper analyzes one of the developments in Colo mbia‘s land organization: the five -year term of Rafael Reyes (1904 -1909). The author examines how a change in territorial division failed because of the tradition of treating the territory as an isolated element, without applying administrative, political, and economic measures that would make development and sustainability possible for all territorial entities.